Utilizing a modified-Postoperative Morbidity Survey for assessing morbidity after laparoscopic or robot-assisted radical prostatectomy: a retrospective observational study - Wenping Peng; Xiaolu Sun; Shuang Zhao; Huimin Hou; Jie Bao (BMC Anesthesiology)
Abstract Background Compared with open radical prostatectomy (RP), laparoscopic or robot-assisted RP have shown a notable decrease in the incidence of organ dysfunction or potentially life-threating complications after surgery. However, despite advances, the postoperative length of hospital stay (LOS) remains longer than desired in many cases. The Postoperative Morbidity Survey (POMS) is a simple approach to detect complications capable of prolonging LOS. The primary objective of this study was to outline the incidence and type of early morbidity following laparoscopic or robot-assisted RP using modified POMS(m-POMS). The secondary objective was to investigate the correlation between m-POMS and postoperative LOS. Methods A retrospective study of the electronic health records was performed for all eligible patients undergoing laparoscopic or robot-assisted RP over a one-year period (August 1, 2022 to July 31, 2023). Morbidity as defined by m-POMS was collected on postoperative day 1 (POD1), POD3, POD5 and POD8. Poisson regression models were employed to assess the correlation between positive m-POMS and postoperative LOS. Results A total of 121 patients were included. Morbidity, as measured by m-POMS, occurred on POD1 (19.01%, 95% CI [13.01%, 26.91%]), POD3 (18.81%, 95% CI [12.39%, 27.52%]), POD5 (30.23%, 95% CI [18.60%, 45.10%]) and POD8 (35.29%, 95% CI [17.31%, 58.70%]). Two prevalent domains with positive m-POMS scores were infectious and pulmonary. The occurrence of morbidity as indicated by m-POMS was correlated with longer median (IQR) postoperative LOS on POD1 7 (5, 9) versus 4 (4, 6), POD3 7 (6, 11) versus 5(4, 6), and POD5 11 (6.5, 11) versus 7(6, 9) (p < 0.05) compared with patients who did not encounter m-POMS-assessed morbidity. Regression analysis showed that m-POMS-defined morbidity was correlated with longer postoperative LOS on POD1 and POD3. Conclusions The incidence of early morbidity, as defined by m-POMS following radical prostatectomy, was approximately 20%, with infectious and pulmonary complications being the most prevalent. Short-term morbidity assessed by m-POMS was significantly associated with prolonged LOS.